Konflik Interpersonal Pasca Konversi Agama di Yayasan Bina Mualaf Medan - Solin, Fajar Dermawan (Islam & Contemporary Issues, 2023)
This article discusses the interpersonal conflicts experienced by individuals after converting to a different religion at the Bina Mualaf Foundation in Medan. The article highlights the importance of religion in society and the freedom to choose one’s own religion. The article also explores the contributing factors to religious conversion and the challenges faced by converts, including conflicts with their families and social environments. The purpose of this article is to analyze the development of interpersonal conflicts experienced by converts and how they seek solutions. The research methodology  mploye dis qualitative, with data collected through interviews and literature reviews. This study focuses on two families at the Bina Mualaf Foundation in Medan. The findings of this study will be analyzed and interpreted to draw conclusions.